2016
DOI: 10.1158/1535-7163.mct-16-0010
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Deacetylase Inhibitor, OBP-801, and Celecoxib Synergistically Inhibit the Cell Growth with Apoptosis via a DR5-Dependent Pathway in Bladder Cancer Cells

Abstract: The prognosis of muscle-invasive bladder cancer with metastasis is poor. There have been no therapeutic improvements for many years, and an innovative therapy for muscle-invasive bladder cancer has been awaited to replace the conventional cytotoxic chemotherapy. Here, we show a candidate method for the treatment of bladder cancer. The combined treatment with a novel histone deacetylase (HDAC) inhibitor, OBP-801, and celecoxib synergistically inhibited cell growth and markedly induced apoptosis through the casp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…We expected that OBP-801 known to suppress survivin [10,11] was an appropriate agent for the combination with eribulin when eribulin was proved to upregulate survivin in TNBC like other microtubule dynamics inhibitors [12]. Our findings showed that the combination treatment of OBP-801 and eribulin induced the synergistic growth inhibition of TNBC cells through apoptosis with the suppression of Bcl-xL and the MAPK pathway as well as survivin.…”
Section: Introductionmentioning
confidence: 72%
“…We expected that OBP-801 known to suppress survivin [10,11] was an appropriate agent for the combination with eribulin when eribulin was proved to upregulate survivin in TNBC like other microtubule dynamics inhibitors [12]. Our findings showed that the combination treatment of OBP-801 and eribulin induced the synergistic growth inhibition of TNBC cells through apoptosis with the suppression of Bcl-xL and the MAPK pathway as well as survivin.…”
Section: Introductionmentioning
confidence: 72%
“…Celecoxib appears to inhibit multiple oncogenic targets and pathways depending on the cancer, including proliferation [24], apoptosis [25], angiogenesis [26], invasion [27], and tumor-induced immune suppression. Some of these pathways are dependent on COX-2, while others are independent of the enzyme [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…4). We previously reported that OBP-801 and celecoxib synergistically induced apoptosis via the DR5-dependent pathway, and that Bim partially acts as one of the key molecules downstream of DR5 in bladder cancer cells (17). Therefore, the DR5-dependent pathway may be partially involved in the caspase-dependent apoptosis by the combination of BGJ398 and OBP-801 in uM-uC-3 cells.…”
Section: Discussionmentioning
confidence: 96%
“…Western blotting. Western blot analysis was carried out as previously described (17). The following antibodies were purchased from the indicated sources: rabbit monoclonal antibodies for anti-Bim (ab32158) (Abcam, Cambridge, uK), anti-Bcl-xL (#2762), and anti-PARP (#9542) (Cell Signaling Technology, Beverly, MA, uSA); rabbit polyclonal antibodies for antisurvivin (AF886) (R&D Systems), anti-DR5 (#8074) (Cell Signaling Technology), anti-DR4 (1139) (ProSci, Inc., Poway, CA, uSA), anti-caspase-3 (#9665), anti-histone H4 (#2935), anti-acetyl-histone H4 (#9672), anti-Bid (#2002), anti-ERK1/2 (#9102), anti-Shp2 (#3752), anti-phospho ERK1/2 (#9101), anti-phospho FRS2-α (#3861), anti-phospho Shp2 (#3751) (Cell Signaling Technology), anti-FRS2-α (SC17841) (Santa Cruz Biotechnology, Dallas, TX, uSA); mouse monoclonal antibodies for anti-caspase-8 (M032-3) and anti-caspase-9 (M054-3) (MBL, Nagoya, Japan), anti-FLIP (ACX-804-961-0100) (Enzo Life Sciences, Farmingdale, NY, uSA), and anti-GAPDH (5G4) (HyTest, Ltd., Turku, Finland) were used as primary antibodies.…”
Section: Detection Of Apoptosismentioning
confidence: 99%